2014
DOI: 10.4103/0019-5049.144643
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the coagulation system

Abstract: Coagulation is a dynamic process and the understanding of the blood coagulation system has evolved over the recent years in anaesthetic practice. Although the traditional classification of the coagulation system into extrinsic and intrinsic pathway is still valid, the newer insights into coagulation provide more authentic description of the same. Normal coagulation pathway represents a balance between the pro coagulant pathway that is responsible for clot formation and the mechanisms that inhibit the same beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
617
0
26

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 712 publications
(643 citation statements)
references
References 39 publications
0
617
0
26
Order By: Relevance
“…Basic coagulation tests were performed for initial characterization of intrinsic and extrinsic pathways of the coagulation system [29] and for detection of overall procoagulant potential of haemostasis [30]. Normally, determination of these parameters is insufficient to characterize the haemostasis system and several additional tests are needed [31].…”
Section: Resultsmentioning
confidence: 99%
“…Basic coagulation tests were performed for initial characterization of intrinsic and extrinsic pathways of the coagulation system [29] and for detection of overall procoagulant potential of haemostasis [30]. Normally, determination of these parameters is insufficient to characterize the haemostasis system and several additional tests are needed [31].…”
Section: Resultsmentioning
confidence: 99%
“…El término proviene de hema (sangre) y estasis (parar), y se refiere al equilibrio trombohemorrágico que se mantiene por interacciones entre la coagulación, el sistema fibrinolítico, las plaquetas y la pared vascular 25 . La activación de la coagulación requiere la participación de plaquetas, endotelio, monocitos y factores de coagulación, y puede ocurrir por las vías extrínseca, intrínseca o ambas, englobadas en el modelo celular de la coagulación 26 .…”
Section: La Hemostasia En El Cáncer Colorrectal Y El Pronósticounclassified
“…Factor VIIa is generated after a cleavage of a single peptide in the protease domain of FVII from a different coagulation enzymes, such as FXa, FIXa, and FVIIa itself. However, FXa seems to be the main activator of FVIIa [6]. It has been shown that the binding of FVII to TF increases its activity by several folds.…”
Section: Coagulation Cascade: Something New?mentioning
confidence: 99%
“…Two different initiator pathways were linked to this model: 1) the "intrinsic pathway, " in which all the clotting factors were present in blood starting from the conversion of FXII to FXIIa induced by the contact to polyanions secreted by activated platelets, and 2) the "extrinsic pathway", in which the subendothelial thrombogenic material, such as TF, was required in addition to circulating components. Both of them resulted in activation of FX and the formation of a fibrin-rich clot through a common pathway [6].…”
Section: Coagulation Cascade: Something New?mentioning
confidence: 99%